MENINGKATKAN HASIL BELAJAR LOMPAT JAUH MENGGUNAKAN RINTANGAN BIOMEKANIK 45° MATA PELAJARAN PENJASORKES PESERTA DIDIK KELAS VI SDN 6 DIRGAHAYU TAHUN PELAJARAN 2019/2020 - Siswoyo Siswoyo (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2021)
research objective was improve student learning outcomes and describe the activities of students learning the 45% biomechanical hurdle long jump. research method is PTK conducted at SDN 6 Dirhahayu, Pulau Laut Utara District, Kotabaru Regency, semester of the 2019/2020 learning year. Students studied class VI with total of 33 children. results study for 2 cycles for 3 months showed fairly good increase in jumping ability. This can be seen from student activities and student learning outcomes in the long jump material. activeness and discipline of students from first cycle was 75% to 92% in the second cycle. Student cooperation learning the first cycle was 75%, second cycle was 92%. Student enthusiasm for learning biomechanical obstacles 45 ° was 83% the first cycle and 92% the second cycle. Meanwhile, student learning outcomes on long jump material with 45 ° biomechanical hurdles in the first cycle were only 84% increased by 94%. This means that classroom action research carried out on long jump material with biomechanical obstacle motivation 45 ° has succeeded in increasing student activity and learning outcomes in long jump material, because the learning outcomes obtained are already above the indicator. Keywords: Long Jump, Biomechanical Barriers 45% and Learning Outcomes.